¿Un tribunal arbitral puede resolver daños a la libre competencia entre particulares en Ecuador? (Tema Central) - Sperber Wilhelm, David (2016)
This essay presents the question of whether private parties can arbitrate damages for abuse of market power (dominant position). We analyzed Ecuadorian arbitration and antitrust legislation. Also, we discussed the relevant doctrine and jurisprudence of the two opposing positions in different countries. Afterward we explore the hypothetical case and its conclusions.